2023
DOI: 10.1002/hed.27441
|View full text |Cite
|
Sign up to set email alerts
|

Detection of laryngeal carcinoma during endoscopy using artificial intelligence

Abstract: BackgroundThe objective of this study was to assess the performance and application of a self‐developed deep learning (DL) algorithm for the real‐time localization and classification of both vocal cord carcinoma and benign vocal cord lesions.MethodsThe algorithm was trained and validated upon a dataset of videos and photos collected from our own department, as well as an open‐access dataset named “Laryngoscope8”.ResultsThe algorithm correctly localizes and classifies vocal cord carcinoma on still images with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 38 publications
0
1
0
Order By: Relevance
“…In 2023, Wellenstein et al reported the results of an AI model to detect carcinoma in images from flexible laryngoscopy and microlaryngoscopy recordings. 10 They were able to analyze images at an average inference frame rate of 63 but only achieved a sensitivity of 71% to 78% using a YOLO model. YOLO models employ a simplified inference algorithm for speed, sacrificing accuracy in the case of specialized datasets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2023, Wellenstein et al reported the results of an AI model to detect carcinoma in images from flexible laryngoscopy and microlaryngoscopy recordings. 10 They were able to analyze images at an average inference frame rate of 63 but only achieved a sensitivity of 71% to 78% using a YOLO model. YOLO models employ a simplified inference algorithm for speed, sacrificing accuracy in the case of specialized datasets.…”
Section: Discussionmentioning
confidence: 99%
“…Artificial intelligence (AI) assisted computer vision during flexible laryngoscopy provides valuable insights and facilitates diagnosis. [7][8][9][10] Investigators have used deep learning models to classify vocal fold pathology, 11,12 localize lesions in the endoscopic field, 13,14 and evaluate images for diagnostic quality. [15][16][17] Most of these applications focus on static endoscopic images; there are few reports of video annotation models.…”
Section: Introductionmentioning
confidence: 99%
“…Now, DL states to an ML method that is dependent upon a neural network (NN) model with numerous data representation stages. Convolutional neural networks (CNNs) constitute feedforward neural networks (FFNNs) with deep architecture and convolution computation [ 8 ]. It has a model that must overcome classification and identification issues.…”
Section: Introductionmentioning
confidence: 99%